Correlation of self-regulation with resilience of non-residential students living in boarding places - Sri Wulan Zari; Krisnova Nastasia; Ummil Khairiyah; Rany Fitriany (Psycho Holistic, 2024)
This study was aimed to determine the correlation of self-regulation with the resilience of non-residential students for Electrical Engineering students at the Padang State Polytechnic. The independent variable in this research was self-regulation and the dependent variable is resilience. The measuring instruments used in this research are the self-regulation scale and the resilience scale. The sample selection technique in this research is a random sampling technique. The sample in this research was 118 Electrical Engineering students’ class of 2022 at Padang State Polytechnic. Item index discrimination and reliability testing in this research used the Cronbach's Alpha technique. The results of the item index discrimination on the self-regulation scale ranged from 0.320 to 0.631. The results of the item index discrimination on the resilience scale ranged from 0.300 to 0.722. Self-regulation reliability coefficient of 0.887 and a resilience scale of 0.893. Based on data analysis, the correlation value between self-regulation and resilience is r = 0.532 (p < 0.05), meaning there is a significant correlation between self-regulation and the resilience of non-residential students for Electrical Engineering students at the Padang State Polytechnic. Correlation in a positive direction show that the higher the self-regulation, the higher the resilience and conversely, the lower the self-regulation, the lower the resilience.